2013
DOI: 10.1115/1.4024862
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Axis Ratio on Fluid Flow Around an Elliptic Cylinder—A Numerical Study

Abstract: The bluff body simulations over canonical forms like circular and square cylinders are very well studied and the correlations for bulk parameters like mean drag coefficient and Strouhal numbers for the same are reported widely. In the case of elliptic cylinder, the literature is very sparse, especially for moderate Reynolds number (Re). Hence, in this work, a detailed study about fluid flow characteristics over an elliptic cylinder placed in a free stream is performed. Simulations are carried out for different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The peaks of the power spectrum at these low frequencies become larger farther downstream, triggering the transition from the two-layered wake to the secondary vortex street. Raman et al 18 conducted twodimensional simulations for the flow around an elliptic cylinder with aspect ratios from 1 to 10 for Reynolds numbers from 50 to 500. They found that the vortex shedding can be suppressed by increasing the aspect ratio for a given Reynolds number.…”
Section: Introductionmentioning
confidence: 99%
“…The peaks of the power spectrum at these low frequencies become larger farther downstream, triggering the transition from the two-layered wake to the secondary vortex street. Raman et al 18 conducted twodimensional simulations for the flow around an elliptic cylinder with aspect ratios from 1 to 10 for Reynolds numbers from 50 to 500. They found that the vortex shedding can be suppressed by increasing the aspect ratio for a given Reynolds number.…”
Section: Introductionmentioning
confidence: 99%
“…Crossflow heat exchanger with elliptic tube arrangement is receiving increased attention, because it produces enhancing heat transfer compared with the other tube cross-section [25][26][27][28][29]. Raman et al [30] simulated flow past unconfined elliptic cylinder with various axis ratios (AR) of 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 and 1, to predict fluid flow characteristics at Reynolds number Re = 50 and Re = 100. The wake sizes behind the cylinder and the coefficient of drag are noticed to enhances with increasing AR but decrease with increase in Reynolds number.…”
Section: Introductionmentioning
confidence: 99%